2012
DOI: 10.1007/s10875-012-9791-z
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Regulates Interleukin-37 in Systemic Lupus Erythematosus

Abstract: The aim of this study was to research the expression of IL-37 in systemic lupus erythematosus (SLE) patients and the effect of glucocorticoid on IL-37. Thirty newly diagnosed severe SLE patients receiving prednisone 1 mg/kg/day for 14 consecutive days and 30 healthy subjects were enrolled into this study. The plasma levels of IL-37 and other cytokines were detected by ELISA and the relative mRNA amounts of IL-37 and other cytokines were detected by RT-PCR. The plasma levels of IL-37, IL-18, IL-18BP, IFN-γ, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 41 publications
10
74
2
3
Order By: Relevance
“…Our study revealed that levels of IL-37 were positively correlated with SLEDAI-2K score which came in agreement with a study done by Song et al (1), 2013. We also found that levels of IL-37 were positively correlated with duration between onset and diagnosis of the disease.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study revealed that levels of IL-37 were positively correlated with SLEDAI-2K score which came in agreement with a study done by Song et al (1), 2013. We also found that levels of IL-37 were positively correlated with duration between onset and diagnosis of the disease.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding was close to the result of a study done by Song et al (1), 2013, where percentage of arthritis was 73.3% and higher than a study done by Abdwani et al (14), 2014, where percentage of arthritis was 62.96%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recent studies revealed that IL37 has a strong anti-inflammatory effect during an innate immune response as well as in the development of inflammation (Nold et al 2010, Banchereau et al 2012. Published literature suggests that IL37 is expressed in various normal tissues, tumors (Pan et al 2001, Kumar et al 2002 and by human peripheral blood mononuclear cells under inflammatory conditions, such as systemic lupus erythematosus (SLE) (Song et al 2013), Behcet's disease (BD) (Ye et al 2014) and acute coronary syndrome (Ji et al 2014). Genetic variants in inflammation-related cytokine genes may have the potential to alter the regulation of transcript production or function.…”
Section: Discussionmentioning
confidence: 99%
“…Wan et al reported that decreased IL-37 expression leads to the increased secretion of pro-inflammatory cytokines including IL-16 and IL-1β in degenerative intervertebraldisc, which suggests a function for IL-37 in delaying the progression of intervertebral disc degeneration (57). It has also been shown that IL-37 expression is significantly higher in the plasma of patients with SLE and that IL-37 suppresses the secretion of pro-inflammatory cytokines in PBMCs of SLE patients (60,73,74). IL-37b expression levels in serum and nasal lavage are significantly increased in children with allergic rhinitis (AR) (14).…”
Section: Chronic Inflammatory and Autoimmune Disordersmentioning
confidence: 99%